Waste toner particles based dispersive solid phase extraction for the trace determination of cadmium in cinnamon tea samples by flame atomic absorption spectrometry - Ali, Busra; Buyuk, Muhammed Ali; Bayraktar, Ahsen; Serbest, Hakan; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2026)
This study presents a dispersive solid phase extraction (DSPE) protocol for the sensitive and accurate determination of trace levels of cadmium ions (Cd2+) by flame atomic absorption spectrometry (FAAS). Toner particles obtained from used printer cartridges were used as sorbent material for preconcentration of Cd2+ ions. Optimization studies were performed univariately for the achievement of the highest extraction efficiency and the limit of detection (LOD) was found to be 0.55 mu g L-1 under optimal operating conditions. By comparing the slopes of the linear plot equations for FAAS and waste toner-based DSPE-FAAS systems, the increase in sensitivity was calculated to be 40.9 times. The feasibility of the developed method was evaluated by spiking recovery studies on cinnamon tea samples and good recovery results between 90.4 % and 119.0 % determined by the matrix matching calibration strategy showed that the method is applicable to cinnamon tea and similar matrices.
Keywords: Cinnamon tea; Cadmium; Waste toner particles; Extraction; Flame atomic absorption spectrometry; PRECONCENTRATION; MICROEXTRACTION; EFFICIENT; SORBENT; LIQUID; COPPER; IONS; FAAS; Chemistry; Food Science & Technology